Comparing the effects of endometrial injury in the luteal phase and follicular phase on in vitro fertilization treatment outcomes - Wang, Yang; Bu, Zhiqin; Hu, Linli (Frontiers in Endocrinology, 2022)
Background Several studies have shown that endometrial injury improves clinical pregnancy outcomes in patients undergoing in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) treatment with a history of implantation failure. However, endometrial injury can be performed in the follicular phase (FP) followed by embryo transfer in the same menstrual cycle or in the luteal phase (LP) before the embryo transfer cycle. Method This prospective cohort study was conducted from January 2015 to September 2021, and a total of 487 patients were included. All included patients had a history of a failed implantation cycle. They were divided into two groups: the FP group (N = 330), in which endometrial injury was performed on menstrual day 3-5, and the LP group (N = 157), in which endometrial injury was performed in the cycle preceding embryo transfer 7 days after ovulation. Results First, in unselected patients, the implantation rate and clinical pregnancy rate were comparable between the LP and FP groups. However, in patients with a history of ≥ 2 failed transfer cycles, the implantation rate was significantly higher in the LP group than in FP group (43.09% versus 33.33%, P = 0.03). Moreover, the clinical pregnancy rate was also significantly higher in patients in the LP group than in patients in the FP group (60.17% versus 46.15%, P=0.02). In addition, logistic regression analysis showed that endometrial injury in the LP group was an independent factor affecting clinical pregnancy outcome in patients with a history of ≥ 2 failed transfer cycles (aOR = 2.05, 90% CI:1.22-3.47, P=0.01). Conclusion Endometrial injury improves pregnancy outcomes when performed in the luteal phase compared with the follicular phase in patients with a history of ≥ 2 failed transfer cycles but not in unselected patients.